Home Sharing and Crime Across Neighborhoods: An Analysis of Austin, Texas - Roth, Jeffrey J. (Criminal justice review, 2021)
Home sharing is an increasingly popular alternative to hotels, in which individuals rent all or a portion of their residence as short-term accommodations for travelers. Criminological research has examined the relationship between crime and visitors in a variety of contexts, but very few studies have explored possible associations between home sharing and crime. Grounded in social disorganization and routine activities theories, this study adds to the literature by evaluating the relationship between home sharing density and several types of crime across census tracts in Austin, Texas. The analysis also controls for the effects of tourism, alcohol establishments, and other relevant sociodemographic factors. The results indicate that the sharing of entire units was not associated with crime rates for any of the offense types. Levels of private rooms, however, were positively associated with one of the offenses. Although far more research is needed on the topic, these results are discussed in light of the other notable study on the topic to suggest early conclusions about home sharing and crime.